KEPENTINGAN INDONESIA MENAIKKAN TARIF IMPOR PRODUK KOSMETIK (STUDI KASUS: KOSMETIK ASAL KOREA SELATAN) - Nada Zahira; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study examines the Indonesian cosmetics market dominated by imported products, especially South Korea. The dominance of the market resulted in the weak existence of local cosmetic products, which resulted in a decline in sales and production.This research uses a mercantilism perspective and the level of analysis of the nation-state is supported by the theory of protectionism. The study is a qualitative research by applying the method of explanatory analysis to find answers and solve a problem to the why question.The final results is Indonesia increases the import tariffs for cosmetic products to reduce the import of cosmetic products and protect the national cosmetics industry by adjusting the policy regulated in PMK No. 110/PMK.010/2018 regarding to collect income tax Article 22 in connection with payments for deposits of goods and activities in the import sector or activities in other fields. The results of this policy have not yielded appropriate results, where imported products still dominate the Indonesian cosmetics market. On the other hand, Indonesia's income could increase. Keywords: national interest, import, economic politic, Indonesia, South Korea, protectionism.